Fully quantum state-resolved inelastic scattering between He and NO(X (2)Pi). - Kłos, J; Aoiz, F; Verdasco, J; Brouard, M; Marinakis, S; Stolte, S (2007)
Quantum mechanical close-coupling calculations have been used to obtain fully quantum state-resolved differential cross sections and opacity functions for the rotationally inelastic collisions of NO(X (2)Pi) with He at collision energies of 63 and 147 meV using the most recent ab initio potential energy surfaces of Kłos et al. [J. Chem. Phys. 112, 2195 (2000)]. Double peaks observed in the Lambda-doublet resolved differential cross sections are shown to be related to the presence of analogous peaks in the corresponding opacity functions. These structures can be linked directly to a specific expansion term in the potential, and reflect the fact that NO is not quite homonuclear.